2017
DOI: 10.1016/j.cogpsych.2016.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Today is tomorrow’s yesterday: Children’s acquisition of deictic time words

Abstract: Deictic time words like "yesterday" and "tomorrow" pose a challenge to children not only because they are abstract, and label periods in time, but also because their denotations vary according to the time at which they are uttered: Monday's "tomorrow" is different than Thursday's. Although children produce these words as early as age 2 or 3, they do not use them in adult-like ways for several subsequent years. Here, we explored whether children have partial but systematic meanings for these words during the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
57
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 62 publications
4
57
0
2
Order By: Relevance
“…Although past studies have shown that preschoolers can use explicit timelines and other physical artifacts to coarsely differentiate the times of events, this typically required adult demonstrations and extensive explanation (Busby Grant & Suddendorf, 2009;Friedman, 2000Friedman, , 2002Friedman & Kemp, 1998;Friedman, 2000Friedman, , 2002Tillman, Marghetis et al, 2017). Spatial priming was strikingly effective, given how minimal the intervention was.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although past studies have shown that preschoolers can use explicit timelines and other physical artifacts to coarsely differentiate the times of events, this typically required adult demonstrations and extensive explanation (Busby Grant & Suddendorf, 2009;Friedman, 2000Friedman, , 2002Friedman & Kemp, 1998;Friedman, 2000Friedman, , 2002Tillman, Marghetis et al, 2017). Spatial priming was strikingly effective, given how minimal the intervention was.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, although several studies have asked how children map time onto external spatial artifacts (e.g., Berteletti, Lucangeli, & Zorzi, 2012;Busby Grant & Suddendorf, 2009;Friedman, 2000Friedman, , 2002Friedman & Kemp, 1998;Hudson & Mayhew, 2011;Tillman, Marghetis, Barner, & Srinivasan, 2017), and others have examined the direction of children's counting (e.g., Göbel, McCrink, Fischer, & Shaki, 2018;Shaki, Fischer, & Göbel, 2012), only two previous studies have tested whether children produce LR representations of time in the absence of training or experimentally imposed artifacts that force the use of a line. One study (Dobel, Diesendruck, & Bölte, 2007) showed that while adults and literate children tended to represent the agent, object, and recipient in a verbally described event congruently with their reading/ writing direction, preschoolers did not show this bias.…”
Section: Research Highlightsmentioning
confidence: 99%
“…Tillman, Marghetis, Barner, and Srinivasan (2017) have demonstrated that while 6-year-olds rarely make errors about the deictic status of the sort of time words used in the current study, knowledge about the relative remoteness of temporal locations improves considerably between 6 and 8 years. Disentangling the precise effect that age has on marking magnitude is difficult because there were age group differences in the relative proportion of lateral to sagittal gestures, with magnitude being more likely to be marked in the former than the latter axis.…”
Section: Interpreting the Developmental Findingsmentioning
confidence: 52%
“…If we limit our analysis to just instances where participants produced two spatial gestures in the lateral axis, we see a difference between the adults and the three younger age groups, with adults more likely to mark magnitude differences in their gestures than each of the children groups. Tillman, Marghetis, Barner, and Srinivasan (2017) have demonstrated that while 6-year-olds rarely make errors about the deictic status of the sort of time words used in the current study, knowledge about the relative remoteness of temporal locations improves considerably between 6 and 8 years. This suggests that the youngest children may have marked magnitude less than adults because they had a less firm grasp on the relative magnitudes of the distances.…”
Section: Interpreting the Developmental Findingsmentioning
confidence: 52%
“…As H&M point out, simply being able to say temporal words should not be taken as evidence that children fully understand them, or that they have TR capacities that would allow this. Relevant to this, beyond the early studies of "before" and "after," more recent research has examined children's acquisition of additional classes of time words Busby-Grant & Suddendorf 2011;Shatz et al 2010;Tillman & Barner 2015;Tillman et al 2017;Zhang & Hudson 2018a). These other lexical categories are linked to key facets of the adult TR system.…”
Section: Introductionmentioning
confidence: 99%